MODEL PERTAHANAN JEPANG DI KABUPATEN LUMAJANG DAN JEMBER, JAWA TIMUR: TIPOLOGI DAN ARAH SASARAN - Chawari, Muhammad (BRIN, 2015)
This paper is based on research conducted by Yogyakarta Archaeological Center in 2013 with the theme of the Japanese Defense Facilities In The World War II in Lumajang and Jember. The research is an effort to disclose the typology of Japanese defense facilities well as their coverage in both locations. At both locations have been identified 43 objects from the era of Japanese occupation, consisted of bunker (40 objects), cave (2 objects), and water tank (1 object). Among them, 38 objects commanded the sea traffic, 4 objects commanded land routes, and 1 object is unknown.